Appendix to A Field Study of Refactoring Rationale, Benefits, and Challenges at Microsoft - Kim, Miryung; Zimmermann, Thomas; Nagappan, Nachiappan; Nagappan, Nachi; Zimmermann, Tom (Microsoft Research, 2012)
In order to understand refactoring practices at Microsoft, we sent a survey to 1290 engineers, whose change comments include a keyword, "refactoring" in the last 2 years for five Microsoft products (Windows Phone, Exchange, Windows, Office Communication and Services, and Office). We purposely targeted the engineers who are already familiar with the term, "refactoring," because our goal is to understand their own refactoring definition and their perception about the value of refactoring. This document contains the complete set of survey questions. The results of the survey will be published in a separate paper.